Comparison of Application Effects of Different Hemostasis Methods After Ischemic Cerebrovascular Intervention - Zhou, Yanli; Xu, Chenghua (Frontiers in Surgery, 2022)
To explore the effects of two different hemostasis methods, namely arterial compression device and vascular closure devices, in ischemic cerebrovascular intervention, so as to provide a theoretical basis for clinical selection of hemostasis methods. A total of 302 patients who underwent ischemic cerebrovascular intervention in our hospital from January 2016 to December 2020 were selected as the research subjects and randomly divided into the control group (n=151) and the observation group (n=151). Patients in both groups underwent cerebrovascular intervention. Patients in the control group were treated with artery compressor for hemostasis after operation, while those in the observation group were treated with vascular closure devices for hemostasis. The hemostatic indexes and vascular parameters at the puncture site before and after the operation were compared between the two groups. The comfort level of the patients was assessed at 6h, 12h and 24h after operation with Kolcaba Comfort Scale score, and the postoperative complications were recorded. Results: For patients with ischemic cerebrovascular disease undergoing femoral artery puncture intervention, the use of vascular closure devices can stop bleeding quickly, which can significantly shorten the bleeding time, and the postoperative braking time of patients is short, with high comfort and less complications.